Ion and electron motions in the outer electron diffusion region of collisionless magnetic reconnection - Cong Chang; QuanMing Lu; San Lu; Kai Huang; RongSheng Wang (Earth and Planetary Physics, 2024)
Two-dimensional particle-in-cell simulations are performed to study the coupling between ion and electron motions in collisionless magnetic reconnection. The electron diffusion region (EDR), where the electron motions are demagnetized, is found to have a two-layer structure: an inner EDR near the reconnection site and an outer EDR that is elongated to nearly 10 ion inertial lengths in the outflow direction. In the inner EDR, the speed of the electron outflow increases when the electrons move away from the X line. In the outer EDR, the speed of the electron outflow first increases and then decreases until the electrons reach the boundary of the outer EDR. In the boundary of the outer EDR, the magnetic field piles up and forms a depolarization front. From the perspective of the fluid, a force analysis on the formation of electron and ion outflows has also been investigated. Around the X line, the electrons are accelerated by the reconnection electric field in the out-of-plane direction. When the electrons move away from the X line, we find that the Lorentz force converts the direction of the accelerated electrons to the x direction, forming an electron outflow. Both electric field forces and electron gradient forces tend to drag the electron outflow. Ion acceleration along the x direction is caused by the Lorentz force, whereas the pressure gradient force tends to decelerate the ion outflow. Although these two terms are important, their effects on ions are almost offset. The Hall electric field force does positive work on ions and is not negligible. The ions are continuously accelerated, and the ion and electron outflow velocities are almost the same near the depolarization front.